THE SOCIO-PHILOSOPHICAL INTERPRETATION OF DEVELOPING STUDENTS’ CREATIVE THINKING IN THE NEW UZBEKISTAN - Sayfutdinovna, Abdullayeva Barno (Journal of Higher Education and Academic Advancement, 2025)
Objective: This article provides an in-depth analysis of the socio-philosophical interpretation of the formation of students' creative thinking in the conditions of New Uzbekistan, emphasizing its importance during the post-independence period marked by large-scale reforms, modernization of the education system, development of human capital, and the implementation of the principle of "New Uzbekistan – new thinking" aimed at nurturing creative and initiative-driven individuals who strive to create innovations. Method: The study analyzes the content of the concept of creative thinking, its social and philosophical essence, and its role in the development of the individual through a socio-philosophical lens, interpreting it not merely as a mental process but as a complex phenomenon reflected in an individual’s social activity. Result: The article reveals the philosophical foundations, social content, and practical directions of the process of forming creative thinking, identifying how creative thinking contributes to the shaping of innovative and socially active individuals within the framework of Uzbekistan’s modernization. Novelty: The study’s originality lies in its exploration of the historical roots of creative thinking development by connecting it with the philosophical heritage of prominent Eastern thinkers such as Abu Nasr Farabi, Alisher Navoi, Ahmad Donish, and Abdulla Avloni, thereby linking classical philosophical ideas with contemporary educational reform in New Uzbekistan.